Finding my way : a memoir - Yousafzai, Malala, 1997- (Atria Books, 2025)
"How do you rebuild yourself when your whole world changes overnight? Thrust onto the public stage at fifteen years old after the Taliban's brutal attack on her life, Malala Yousafzai quickly became an international icon known for bravery and resilience. But away from the cameras and crowds, she spent years struggling to find her place in an unfamiliar world. Now, for the first time ever, Malala takes us beyond the headlines in Finding My Way--a vulnerable, surprising memoir that buzzes with authenticity, sharp humor, and tenderness. Finding My Way is a story of friendship and first love, of anxiety and self-discovery, of trying to stay true to yourself when everyone wants to tell you who you are. In it, Malala traces her path from high school loner to reckless college student to a young woman at peace with her past. Through candid, often messy moments like nearly failing exams, getting ghosted, and meeting the love of her life, Malala reminds us that real role models aren't perfect--they're human. In this astonishing memoir, Malala reintroduces herself to the world, sharing how she navigated life as someone whose darkest moments threatened to define her narrative--while seeking the freedom to find out who she truly is. Finding My Way is an intimate look at the life of a young woman taking charge of her destiny--and a deeply personal testament to the strength it takes to be unapologetically yourself."--